2021
DOI: 10.1021/jacs.0c12819
|View full text |Cite
|
Sign up to set email alerts
|

Fast Carbon Isotope Exchange of Carboxylic Acids Enabled by Organic Photoredox Catalysis

Abstract: Carbazole/cyanobenzene photocatalysts promote the direct isotopic carboxylate exchange of C(sp 3 )-acids with labelled CO2. Substrates that are not compatible with transition metal catalyzed degradation-reconstruction approaches or prone to thermally induced reversible decarboxylation undergo isotopic incorporation at room temperature in short reaction times. The radiolabelling of drug molecules and precursors with [ 11 C]CO2 is demonstrated.The synthesis of isotopically labelled molecules is essential to drug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 60 publications
1
51
0
1
Order By: Relevance
“…These data are consistent with turnover limiting photoreduction of 30 and minimal catalyst decomposition or product inhibition (see SI for details). As with NpMI , addition of 31 excluded product inhibition and suggests 4‐DPAIPN decomposition occurs [99–102] but is attenuated relative to NpMI . These data indicate that the improved performance of 4‐DPAIPN can be attributed to it forming a more robust electron‐primed photoredox catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…These data are consistent with turnover limiting photoreduction of 30 and minimal catalyst decomposition or product inhibition (see SI for details). As with NpMI , addition of 31 excluded product inhibition and suggests 4‐DPAIPN decomposition occurs [99–102] but is attenuated relative to NpMI . These data indicate that the improved performance of 4‐DPAIPN can be attributed to it forming a more robust electron‐primed photoredox catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…[44] Very recently,t he group of Rotstein and Lundgren reported an ew method for direct isotopic carboxylate exchange by using cyanoarene catalyst PC10. [45] It turns out that an alkylative decyanation of PC10 by phenylacetic acid takes place in situ to yield the more-active catalyst PC18.The authors demonstrated that the exchange process takes place under an atmospheric pressure of 13 CO 2 .T he labeling of primary,s econdary,a sw ell as tertiary carboxylic acid derivatives occur under mild reaction conditions.I nterestingly,t he substrate contains aw ide variety of complex functional groups of high interest. More interestingly,t he concept was extended to 11 C-labeling with 11 CO 2 under catalytic conditions of PC18,w hich actually constitutes abreakthrough in radiolabeling applications (Scheme 31).…”
Section: Carboxylationsmentioning
confidence: 99%
“…Forschungsartikel rapid deactivation of NpMI under these conditions.I ns tark contrast, an analogous "same excess" experiment with 4-DPAIPN resulted in clean first order reaction profiles that nearly overlay.T hese data are consistent with turnover limiting photoreduction of 30 and minimal catalyst decomposition or product inhibition (see SI for details). As with NpMI,a ddition of 31 excluded product inhibition and suggests 4-DPAIPN decomposition occurs [99][100][101][102] but is attenuated relative to NpMI.T hese data indicate that the improved performance of 4-DPAIPN can be attributed to it forming am ore robust electron-primed photoredox catalyst. Indeed, the initial rate of dehalogenation promoted by NpMI is faster than 4-DPAIPN but rapid decomposition of this catalyst renders it ineffective for more challenging substrates that are slower to fragment following reduction.…”
Section: Angewandte Chemiementioning
confidence: 99%